Population structure of commercially important groupers in the coral triangle Gorontalo, Indonesia to support conservation - DEWI SHINTA ACHMAD; MUH. SALEH NURDIN; IVAN TASLIM; ABIGAIL M. MOORE (Society for Indonesian Biodiversity, 2023)
Abstract. Achmad DS, Nurdin MS, Taslim I, Moore AM. 2023. Population structure of commercially important groupers in the coral triangle Gorontalo, Indonesia to support conservation. Biodiversitas 24: 6592-6601. Appropriate management units are fundamental to the conservation of species and ecosystems. In the case of exploited fishes, sustainable approaches to fisheries management are generally based on population units (stocks). This study aimed to address the lack of data to define the population structure of the stocks of two commercially important grouper species (Variola albimarginata (Baissac, 1953) and Variola louti (Forsskål, 1775)) in the Sulawesi Sea and Tomini Bay waters of Gorontalo Province, Sulawesi, Indonesia, in the Wallacea biodiversity hotspot. We used a combined morphometric and molecular (DNA barcoding, COI marker). We used truss network analysis with 14 characters to evaluate inter and intraspecies morphometric differences. DNA was extracted (Qiagen protocols) from tissue samples from individuals of both species in both sea areas, followed by polymerase chain reaction (PCR) and Sanger sequencing. Sequence processing and phylogenetic analyses conducted in MEGA X. Both approaches show clear separation between V. albimarginata and V. louti but indicate close kinship between the north coast (Sulawesi Sea) and south coast (Tomini Bay) populations of these groupers. Under the authority of the Gorontalo Province Marine and Fisheries Service, these two populations could be managed as one stock without compromising fisheries sustainability or the conservation of these ecologically and economically valuable species.